THE EPIC OF THE SUBALTERN: REVOLUTION, RESISTANCE AND REGRESSION IN VALSALA’S AGRARIAN TRILOGY - S. Jayan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This article explores the political and socio-historical significance of Valsala’s agrarian trilogy, Nellu, Agneyam and Koomenkolli, as a literary cartography of subaltern struggle in Wayanad. Tracing the evolution of Kerala’s peasant movements through fiction, the study highlights how Valsala documents the trajectory from feudal oppression to revolutionary fervour, and finally, to post-revolutionary disillusionment. Employing a close reading of key characters and their narrative functions, the article demonstrates how the author crafts a powerful political discourse rooted in agrarian realities, echoing the ideological concerns of revolutionary leaders such as Charu Majumdar. In doing so, the study positions Valsala’s work as a critical site for understanding subaltern agency, political education, and the historical limits of idealism in postcolonial India.